Sex hormones and choice under risk - Burkhard C. Schipper (University of California, Department of Economics, 2014)
We study the correlation of choice under risk in Holt-Laury lotteries for gains and losses with gender, the use of hormonal contraceptives, menstrual cycle information, salivary testosterone, estradiol, progesterone, and cortisol as well as the digit ratio (2D:4D) in more than 200 subjects. In males, salivary testosterone is negatively correlated with risk aversion for gains only. In females, salivary cortisol is positively correlated with risk aversion for gains only. No other significant correlations between risk preferences and salivary hormones are observed. No significant correlations between risk preferences and the menstrual cycle are observed in naturally cycling females. No significant correlations between risk preferences and the digit ratio are observed in either gender and/or race. Females who use hormonal contraceptives are more likely to make ``consistent'' choices although this may be due to a selection effect. Risk aversion is positively correlated with being female for losses only.
Keywords: C91; C92; D44; D81; D87; 330; hormones; menstrual cycle; contraception; digit ratio; 2D:4D; gender; endocrinological economics; Holt-Laury; risk aversion; risk seeking; reflection effect; prospect theory